REVISED TRAUMA SCORE AS A PREDICTOR OF OUTCOME IN TRAUMA CASES: EXPERIENCES AT A TERTIARY CARE HOSPITAL IN KARACHI, PAKISTAN - Mohyuddin, Ghulam Rehman; Alam, Zakariya; Malik, Umair Zafar; Shakil, Omair; Haq, Anwar Ul (Journal of Ayub Medical College Abbottabad, 2015)
Background: Trauma scores help classify trauma patients, and assist in clinical decision-making. The Revised Trauma Score (RTS) is widely used internationally but its effectiveness as a tool for predicting outcome in paediatric trauma patients in our setting, has yet to be established, mainly owing to lack of use. The aim of this study was to determine the effectiveness of RTS as a predictor of outcome in paediatric trauma patients in Pakistan. Methods: We conducted a retrospective review of patient medical records at Aga Khan University Hospital, Karachi, from October 2006 to October 2009 and all patients aged less than 14 years, presenting with trauma were selected. Information was collected regarding demographics, vital signs at the time of presentation, length of stay (LOS) in the ward, ICU and the hospital, complications during hospital stay and mortality. Data was analysed in SPSS-17.0. Results: The sample was 501 patients with a mean age of 5.3 years. Two third (66%) were males and 34% were females. Using available data, RTS was calculated for 394 patients, who were then divided into two groups based on the RTS. For 32 patients with a RTS less than 10, the length of stay in the ward, ICU and the hospital were all shorter than the 363 patients with a RTS greater than 10 (p-value <0.001). Conclusion: In our setting, RTS is a good predictor of outcome in paediatric trauma patients. It can aid in the assessment of severity of injury in, and objective assessment and triaging of paediatric trauma patients.